Molecular Approaches for Assessing Some Iranian Freshwater Fish Species - Elham Mirahmadi Seyed; Saeed Heydaranjad Mohammad; Hashemzadeh Saqrlou Iraj; Narjes Tabatabai Seyed (Journal of Zoological Research, 2025)
Monitoring fish biodiversity and its changes over time and their ecological research is one of the important sources of information in their protection. They can be used to find fish biodiversity at different times, such as the capture and maintenance of whole fish, genetic samples, or the use of scales. In this regard, to check the prepared sample, 10-15 scales were prepared from the area of the lid, dorsal fin, and tail stem. Then, they were treated in 5% potassium solution and settled on a slide using a loop microscope equipped with a camera. Among the examined species, Luciobarbusbraczcephalus, Luciobarbuscapito and Capoetasaadispecies could be distinguished from other species with the highest accuracy. In the genetic studies conducted using the cytochrome oxidase subunit 1 gene, the patterns observed in the neighbor joining genealogical tree were consistent with the differences in the genera and species studied. The results of this investigation show that the origin of species can be determined with more than 50% accuracy using genetic data.
Keywords: Freshwater fishes